Evaluation of Antibiotic Utilization in Respiratory Tract Infections Using ATC/DDD and Gyssens Methods - Samirah Samirah; Maria Oktavia; Noer Qonita; Risa F Musawaris; Mareta Rindang (Interdisciplinary Social Studies, 2026)
Respiratory tract infections affect both the upper and lower respiratory tract and remain a major global health problem, with pneumonia prevalence reaching around 23% across all age groups. The high incidence often leads to increased antibiotic use, which may contribute to antimicrobial resistance if used inappropriately. Therefore, antimicrobial stewardship (AMS) programs are essential to monitor and optimize antibiotic use in hospitals. This study aimed to analyze antibiotic utilization in patients with respiratory tract infections using the Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) method and the Gyssens method at Dr. Soedarso Regional General Hospital, Pontianak. A prospective observational study was conducted using medical record data of 248 inpatients aged ?18 years who received antibiotic therapy during January–December 2023. The results showed that most patients were male (62.9%). Quantitative analysis indicated that Ceftriaxone and Levofloxacin were the most frequently used antibiotics based on DDD/100 patient-days. Qualitative evaluation using the Gyssens method revealed that most antibiotic use was appropriate, although some cases still showed inappropriate indications, duration, alternative therapy selection, and timing of administration.